QUALITATIVE RELATIONSHIPS OF WATER MIGRATION IN HIGHWAY EMBANKMENT CLAY SOILS BY THE RESULTS OF LABORATORY AND FIELD RESEARCH (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
As a result of quantitative data analysis by laboratory and field experiments quantitativepatterns of water migration in compacted silty loam embankment, including the stabilized (orfinal) clay soil moisture values, depending on their type (number plasticity), soil skeletondensity, embankment height and time «rest» of the subgrade before it’s operation areestablished. The soil moisture changes graphs at what the loam was compacted from soilskeleton density and stabilized soil moisture of already compacted loam after the subgrade«rest» from soil skeleton density are plotting in the article. The empirical dependence ofcompacted silty loams stabilized moisture for their multilayer consolidation is obtained.Empirical dependence parameter corresponds to maximum molecular moisture capacity atwhat it is advisable to do the subgrade clay soils multilayer consolidation for the ensuring theirlong-term strength.Keywords: water migration, compacted loam, soil skeleton density, plasticity number,stabilized moisture, two-factor analysis, empirical dependence.